TRANSFORM: A MODEL OF FELDA YOUTH LEADERSHIP DEVELOPMENT - Amir, Aris; Ahmad Rozelan, Yunus (2012)
The Federal Land Development Authority (more commonly referred to as FELDA) is a Malaysian government agency handling the resettlement of rural poor into newly developed areas. It focuses on opening smallholder farms growing cash crops. FELDA is the world's largest plantation operator, with 811,140 hectares (2,004,400 acres) of oil palms. Being as a huge resettlement residence area, FELDA settlers is a huge community which should be managed based on principles of HRM. In addition, human capital development has become an essential component in the nation development process. This is due to the fact that any development process is driven by the human factor. This project presents a model of the human capital development / training among FELDA Land Scheme Youth in Malaysia. Its main goal is to develop a training model which might be used to facilitate transformation of leadership skills among Youth. The Model based by experiential learning approach consist of modules that develop leadership skills involved psychology domain and human capital development concepts. The model is known as TRANSFORM. The main idea behind this training model is to help participants to better understand their own self and environment. The main characteristics which make this training model unique are the simulation activities are tailored-made to the participants’ specific self and needs. Theoretical and practical applications include psychometric testing, self esteem development and team work skills development. The case studies of this project have reported positive training effects on the participants and on the organization. The cost-effectiveness analysis has revealed significant advantages of TRANSFORM model.